Manajemen English Fun Day Berbasis Game-Based Learning untuk Peningkatan Kosakata dan Simple Past Tense Siswa - Ani, Adriani; Fadilla, Aynun; Dahniar, Dahniar; Chryselia, Dhea; Utami, Dian Putri; Gusfiani, Gusfiani; Haslinda, Haslinda; Bulawan, Santi; Junaedi, Ahmad (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The activity was conducted at SMPN 04 Majene in two sessions, namely on November 14, 2025, for Grade VIII students and on November 21, 2025, for Grade IX students, with a total of 40 participants. The implementation method included a preparation stage consisting of developing instructional materials, selecting 40 regular and irregular verb vocabularies as the focus of learning, and creating flashcards as learning media. The implementation stage began with the delivery of basic Simple Past Tense material and vocabulary introduction, followed by core activities in the form of two educational games: a group-forming game based on vocabulary and a flashcard searching competition for Verb 1 according to sentence clues in the Simple Past Tense form. The results of the activity showed that students were able to improve their ability to accurately identify verb forms, understand the patterns of regular and irregular verb changes, and use vocabulary in simple sentence contexts. Overall, the implementation of English Fun Day proved to be effective in creating a fun and interactive learning atmosphere and in significantly enhancing students’ vocabulary mastery.